Improving Drug Literacy Among Students Through the DAGUSIBU Educational Program - Defilia Anogra Riani; Ahmad Irawan; Shesanthi Citrariana; Shavira Alpasa Hakim; Nazifa Wulan Pritaningtyas; Galang Rizdho Desindria; Jonathan Kaharati (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
Low public literacy regarding the correct application of the DAGUSIBU (Obtain, Use, Store, and Dispose) principles of drugs contributes to the persistently high prevalence of irrational drug use in Indonesia. This situation has the potential to lead to drug abuse, antibiotic resistance, and negative impacts on public health. This community service activity aims to improve the knowledge and rational drug use behavior of 10th-grade students at SMA Negeri 2 Palangka Raya regarding safe and responsible drug management. The methods used include interactive outreach through educational media, practical simulations, and evaluation using pre- and post-tests. The target group was 35 10th-grade students at SMA Negeri 2 Palangka Raya. The results showed an increase in student understanding with an average pre-test score of 6.9 to 7.6 on the post-test (maximum score of 8) regarding the DAGUSIBU principles, which were delivered directly through practice and active discussion. The conclusion of this activity is that the interactive DAGUSIBU outreach is effective in improving understanding of drug literacy and fostering more responsible drug management behaviors in students, which have a positive impact on reducing the risk of drug abuse and supporting individual and environmental health.